A true marriage of opposites (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2020)
Questions of censorship and self-censorship are confronted through JuliaVarley’s experience of animating a skull mask on stilts, Mr. Peanut, and a puppet,Sheherazade. Mr. Peanut travels to many Latin American countries, and the article remembers episodes from Ayacucho, Perú, and Santiago de Chile, and the meetings with soldiers and police.